2020
DOI: 10.3390/rs12152439
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intra-Annual and Inter-Annual Variabilities of Soil Erosion in Crete Island (Greece) by Incorporating the Dynamic “Nature” of R and C-Factors in RUSLE Modeling

Abstract: Under the continuously changing conditions of the environment, the exploration of spatial variability of soil erosion at a sub-annual temporal resolution, as well as the identification of high-soil loss time periods and areas, are crucial for implementing mitigation and land management interventions. The main objective of this study was to estimate the monthly and seasonal soil loss rates by water-induced soil erosion in Greek island of Crete for two recent hydrologically contrasting years, 2016 (dry) and 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 48 publications
(73 reference statements)
0
35
0
Order By: Relevance
“…In Greece, the farming practice for areas exceeding 10% slope is the cultivation along or diagonal to the contour (cross slope contour farming) in order to conserve rainwater and to reduce soil losses [19]. In Crete, the main conservation support practices are contour farming, stone walls, and grass margins [1]; thus, these three types of support practices were considered to estimate the P-factor. The following table (Table 1) summarizes the input dataset required for RUSLE model.…”
Section: Datamentioning
confidence: 99%
See 3 more Smart Citations
“…In Greece, the farming practice for areas exceeding 10% slope is the cultivation along or diagonal to the contour (cross slope contour farming) in order to conserve rainwater and to reduce soil losses [19]. In Crete, the main conservation support practices are contour farming, stone walls, and grass margins [1]; thus, these three types of support practices were considered to estimate the P-factor. The following table (Table 1) summarizes the input dataset required for RUSLE model.…”
Section: Datamentioning
confidence: 99%
“…Both slope length and steepness are proportional to erosion. Consequently, increases in L and S lead to higher runoff velocities and higher soil loss rates [1]. These topographic parameters are so sensitive to soil loss that a minor miscalculation could lead to inaccurate assessment of the overall soil erosion rates.…”
Section: Rusle Model 231 Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The steep orography has a strong effect on the precipitation regimen, with large orographic precipitation effects to be observed [17][18][19][20] that, in combination with its location within the Mediterranean, have resulted in numerous heavy precipitation events that were followed by serious flooding events, such as those which occurred in the Giofiros region in 1994 [17,21], in the Almirida region in 2007 [22,23], as well as February 2019 s extensive flooding in the Chania prefecture [24] and floods in the southern parts of the island [25]. Recent findings have indicated that the region's precipitation regime facilitates rainfall induced soil erosivity to a larger extend than was previously thought [26,27]. From a hydrogeological perspective, the island is mainly composed of pre-alpine and alpine carbonate formations and neogene and quaternary (alluvial) sediments which expedite water penetration; hence, the region exhibits limited surface water resources [28].…”
Section: Case Study Regionmentioning
confidence: 99%